Božidar Kos - Ribizel, Tjaša (Muzikološki zbornik, 2014)
Božidar Kos, composer, teacher and theorist, has through his work, become worldwide known. His compositional output is variegated, intended for different setting, which include also his chamber works. This part of his oeuvre is presented by a detailed wxamination of his String Quartet.
Keywords: 20.st.; komorna dela; Kos, Božidar, 1934-; Kos, Božidar: String Quartet